VIDEO COMPANY PROFILE SEBAGAI STRATEGI PROMOSI POTOKITA SELF STUDIO - Jerricho Ivandro Ekklesia; Yunita Indinabila (LPPM Stikosa-AWS, 2025)
The digital era has driven the emergence of the increasingly popular self-photo studio trend. ”Potokita Self Studio